A competency framework for Ph.D. programs in health information management. (December 2022) - Ahmadi, Maryam; Sheikhtaheri, Abbas; Tahmasbi, Foziyeh; Eslami Jahromi, Maryam; Rangraz Jeddi, Fatemeh
Highlights: There are no competency frameworks specifically developed for Ph.D. educational programs in health information management (HIM). We developed a competency framework for Ph.D. educational programs with the participation of faculty members and students/graduates in HIM. This framework suggests a list of competencies in 11 domains and 71 sub-domains. This framework considers the transition of HIM practices to digital health and health information technologies. Abstract: Introduction: The job expectations and professional competencies required by health information management (HIM) students/graduates are constantly changing and workforce development requires curricula in line with new emerging competencies. Although there are some competency frameworks in this field, there is no one specifically for Ph.D. educational programs in HIM. We aimed to develop a competency framework for Ph.D. programs in HIM in Iran. Methods: We firstly developed a list of competencies based on those published in the literature or by related associations in nine domains and 51 sub-domains. We used the modified Delphi technique and invited Ph.D. students/graduates in HIM and related faculty members throughout the country to participate. Competencies with more than 75% agreement were considered as high priority competencies and those with 50% to 75% agreement as a medium priority. Competencies with less than 50% agreement were dropped. After two rounds, the competency framework was finalized. Results: All suggested competencies were considered a high priority in the first round. Based on suggestions, two new domains (health knowledge management and information technology) and 20 new sub-competencies were added and then accepted in the second round. The final framework includes these competency domains: health data and information management; health data analytics; information technology; teaching competencies; research competencies; health information technology and digital health; health information classifications, terminologies, and ontologies; health information systems governance; managerial competencies; health knowledge management; and digital health entrepreneurship. Conclusion: This framework suggests a list of competencies in 11 domains and 71 sub-domains for Ph.D. students/graduates in HIM that should be considered for the development of future curricula for these educational programs.